2014
DOI: 10.2169/internalmedicine.53.1829
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Pharmacological Therapy of Brugada Syndrome: Is J-wave Attenuation a Marker of Drug Efficacy?

Abstract: We herein describe two patients with Brugada syndrome in whom J-waves were successfully modified by drugs. Case 1 was a 54-year-old man who presented with repeated ventricular fibrillations (VF) and J-point elevation in the right precordial and lateral leads. After administration of cilostazol (200 mg/d), J-waves disappeared and coved-type ST-segment elevation changed to a saddleback-type for 25 months. Case 2 was a 31-year-old man who presented with a VF storm and J-point elevation in the lateral leads. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…117, 119, 120, 124, 318-331 Hermida et al reported 76% efficacy in prevention of VF induced by PES. 119 Belhassen and colleagues 332 recently reported a 90% efficacy in prevention of VF induction following treatment with quinidine, despite the use of very aggressive protocols of extrastimulation.…”
Section: Pharmacologic Approach To Therapymentioning
confidence: 99%
“…117, 119, 120, 124, 318-331 Hermida et al reported 76% efficacy in prevention of VF induced by PES. 119 Belhassen and colleagues 332 recently reported a 90% efficacy in prevention of VF induction following treatment with quinidine, despite the use of very aggressive protocols of extrastimulation.…”
Section: Pharmacologic Approach To Therapymentioning
confidence: 99%
“…Electrical storms (and the associated accentuated J waves) can be suppressed with β‐adrenergic agonists . Chronic oral administration of quinidine, bepridil, denopamine, and cilostazol are reported to prevent VT/VF in both syndromes, probably secondary to inhibition of I to and/or augmentation of I Ca …”
Section: Similarities and Difference Between Brs And Ersmentioning
confidence: 99%
“…47 Hasegawa reported the normalisation of J waves and coved-type ST-segment Clinical Review: Drugs and Devices elevation with VF suppression in a patient who presented with a VF storm after daily administration of 300 mg quinidine and a follow-up of 20 months. 52 These data suggest that low doses of quinidine, which are generally well tolerated, may be useful in controlling arrhythmias.…”
Section: Empiric Quinidine Therapy For Asymptomatic Patientsmentioning
confidence: 93%